(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Research was conducted to create a new algorithm for diagnosing and complex treatment of sepsis in patients with purulent-necrotic complications of diabetes. Purulent-necrotic complications of diabetes in the Andijan regional ADTI clinic and the regional adult health center in the purulent surgical department, to create a new algorithm for diagnosing and complex treatment of sepsis in patients with purulent-necrotic complications of diabetes, to determine the stages of the algorithm for the use of complex treatment of sepsis, and to create a new algorithm for the complex treatment of sepsis.